2012
DOI: 10.1352/1934-9556-50.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Trauma in People with Intellectual and Developmental Disabilities: Reactions of Parents and Caregivers to Research Participation

Abstract: Generally, studies have revealed that only a minority of people are bothered by participation in research on traumatic stress. Severity of traumatic events and subsequent responses are typically unrelated to negative reactions. We included 386 family members and caregivers (respondents) of people with intellectual and developmental disabilities (focus people). Focus people (ages 4-82) had a wide range of physical and intellectual disabilities, medical and behavioral problems, and exposure to potentially trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Studies on the benefits and costs of trauma research now include clinical samples (Carlson et al, 2003;Griffin et al, 2003), medical samples (Newman, Walker, & Cefiand, 1999;Walker et al, 1997), community samples (DePrince & Hebenstreit & DePrince, 2012), and college samples (DePrince & Freyd, 2004;Shorey, Cornelius, & Bell, 2011). This benefit-to-cost pattern also holds for populations viewed as particularly vulnerable, such as children (Chu, DePrince, & Weinzierl, 2008;KassamAdams 8f Newman, 2002, 2005, pregnant women (Schwerdtfeger, 2009;Schwerdtfeger & Nelson Goff, 2008), and individuals with intellectual or developmental disabilities (Scotti et al, 2012). Taken together, the growing body of work suggests that people who disclose their trauma histories as part of research studies generally report positive perceptions of their research experiences.…”
Section: R Esearchers Institutional Review Boardsmentioning
confidence: 99%
“…Studies on the benefits and costs of trauma research now include clinical samples (Carlson et al, 2003;Griffin et al, 2003), medical samples (Newman, Walker, & Cefiand, 1999;Walker et al, 1997), community samples (DePrince & Hebenstreit & DePrince, 2012), and college samples (DePrince & Freyd, 2004;Shorey, Cornelius, & Bell, 2011). This benefit-to-cost pattern also holds for populations viewed as particularly vulnerable, such as children (Chu, DePrince, & Weinzierl, 2008;KassamAdams 8f Newman, 2002, 2005, pregnant women (Schwerdtfeger, 2009;Schwerdtfeger & Nelson Goff, 2008), and individuals with intellectual or developmental disabilities (Scotti et al, 2012). Taken together, the growing body of work suggests that people who disclose their trauma histories as part of research studies generally report positive perceptions of their research experiences.…”
Section: R Esearchers Institutional Review Boardsmentioning
confidence: 99%
“…In addition, TIC acknowledges the likelihood of trauma in the lives of service recipients and service providers (Bloom, ; Harris & Fallot, ). It was previously noted that nearly 80% of individuals with IDD may be exposed to potentially traumatic events (Scotti et al, ) with emerging evidence suggesting similar rates among employed caregivers. For example, Esaki and Larkin () found that 70% of child care workers experienced at least one potentially traumatic event in childhood, approximately 11% higher than had been noted in a population‐based study (i.e., 59.4% of individuals experienced at least one such event; Bynum et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…For example, it has been noted that individuals with IDD are between 3 and 6 times more likely than persons without IDD to be abused or neglected (Hulbert‐Williams et al, ; Soylu, Alpaslan, Ayaz, Esenyel, & Oruc, ; Spencer et al, ; Sullivan & Knutson, ). Scotti et al () reported that 79% of individuals with IDD were exposed to at least one potentially traumatic event, with individuals exposed to, on average, 2.8 events. Further, the types of events that individuals with IDD experience, such as institutionalization, dependency on caregivers and being physically restrained, are likely uncommon in the non‐IDD population (Hulbert‐Williams et al, ; Wigham et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the sensitive nature of the survey and the history of research abuses in this population (210), three questions were included at the end of the survey to assess participant reactions to participating, including: feeling upset, thought worth the time, and felt free to skip questions or stop at any time (457). Responses ranged from not at all to a great deal.…”
Section: Participant Reaction To Participatingmentioning
confidence: 99%